The Process in Language Models (LM) and Their Problems in the Kurdish Language (CK) GPT-4o as an example - Aziz, Assist prof Dr. Omar Ahmed Azeez; Saied, Dr.Mohammed Majeed Saied; Ramadhan, Dr. Hemin Salahaldin Ramadhan (Sulaimani Journal for Humanities, 2025)
The study is entitled ((The Process in Language Models (LM) and Their Problems in the Kurdish Language (CK) GPT-4o as an example )) it attempts to present the processes of language models that each language model follows to generate language and then compare these processes with linguistic theories, whether the processes of generating language models resemble the theoretical mechanisms previously proposed by linguistic theories to analyze language, The research focuses on how Chat GPT-4o has a problem with Kurdish (Central Kurdish) to find out what the problems Kurdish faces are in language models, especially with GPT-4o. We focus more on morphological and syntactical issues that the model faces with Kurdish during the process of tokenization and parsing, the first being more relevant to morphology and the second to syntax.
Keywords: artificial intelligence; language model; tokenization; parsing; GPT4o